Exploring the Use of Oral Corrective Feedback in Turkish EFL Classrooms: A Case Study at a State University - FAKAZLI, Özlem (Kastamonu Egitim Dergisi, 2018)
This classroom-based research investigated how a non-native teacher of English provided corrective feedback to Turkish EFL learners. More specifically, the study aimed to identify language errors produced by the students, corrective feedback types employed by the teacher, and students’ uptake rate following the provided feedback. The data were collected through audio-recording, transcribed, and analyzed in detail for the type of learner errors, type of teacher feedback, and rate of learner uptake. The results revealed that grammatical errors were found to be the most produced error type, and lexical errors were found to be least produced error type. The study also indicated that recast was the most frequently preferred, and clarification request was the least frequently preferred corrective feedback type by the teacher. It was also found that all feedback types led to successful correction of erroneous utterances of the students with 100% learner uptake rate.
Keywords: 4. Education; 10. No inequality; 3. Good health